P72 IS OPEN LEFT THORACO-ABDOMINAL ESOPHAGECTOMY A VIABLE OPTION IN THE ERA OF MINIMALLY INVASIVE ESOPHAGECTOMY?. (23rd November 2019) - Klevebro, F; Boshier, P; Mueller, C; Cools-Lartigue, J; Ferri, L; Low, D
Abstract: Aim: To evaluate short-term and oncological outcomes of left thoracoabdominal esophagectomy compared to minimally invasive esophagectomy for cancer of the esophagus and gastroesophageal junction Background and Methods: Left thoracoabdominal esophagectomy (LTE) facilitates complete resection of esophageal cancer particularly for bulky tumors, but there are concerns that this approach is associated with significant morbidity. Prospectively entered esophagectomy databases from two high volume North American centers were reviewed for patients undergoing LTE or MIE in the 2012-2018. Patient demographics, tumour characteristics, operative outcomes, postoperative outcomes, and pathologic surrogates of oncologic efficacy (R0 resection rate, and number of resected lymph nodes) were compared. Results: In total 247 patients were included in the study, LTE was applied in 170 (68.8%) patients, and MIE in 77 (31.2%) patients. LTE patients had more neoadjuvant treatment (LTE=78.2%, MIE=34.2%, P<0.001). There was no difference in overall postoperative complications (LTE=56.9%, MIE=55.0%, P=0.799), severe complications (Clavien Dindo>2 - LTE=26.1%, MIE17.0%, P=0.184), pulmonary complications (LTE=31.9%, MIE=20.0%, P=0.085), pneumonia (LTE=15.2%, MIE=13.6%, P=0.768), anastomotic leak (LTE=7%, MIE=10%, P=0.396), or postoperative mortality (LTE=0%, MIE=1.3%, P=0.140). Median length of stay was 7 days in both groups. R0 resection rate was 93.8% and 95.5% respectively (P=0.631). Median number of resected lymph nodes was 24 for LTE and 22 for MIE (P=0.226). LTE had more stage II-IV tumors (LTE=67.8%, MIE=40.7%, P<0.001), and more node positive resections (LTE=52.5%, MIE=31.4%, P=0.003). Conclusion: LTE was used for larger tumors with greater lymph node burden in patients that were more likely to have received neoadjuvant treatment compared to MIE. Despite this the postoperative morbidity was equal to that of MIE, with no difference in short-term or oncological results in this cohort.